Efektivitas Model Kooperatif Tipe Jigsaw terhadap Pemahaman Konsep Matematika pada Materi Statistika Kelas X di MAN 01 Alor - Amsidi, Mukmin (STKIP Muhammadiyah Kalabahi, 2025)
This study investigates the effectiveness of the Jigsaw cooperative learning model in enhancing students’ conceptual understanding of statistics in Grade X at MAN 01 Alor. Two classes participated: an experimental class using the Jigsaw model and a control class using traditional teaching. Pre-test scores were comparable (55 vs. 56), but post-test results showed a significant improvement in the experimental class (78) compared to the control (65). The 23-point gain in the experimental group versus 9 points in the control group indicates the Jigsaw model's positive impact. The model encourages peer teaching, active participation, and deeper understanding. These findings support previous research (Slavin, 2018; Çakır & Akbulut, 2022) and suggest Jigsaw is effective, especially in 3T (remote and underdeveloped) regions like Alor. It highlights the potential of student-centered learning in improving mathematics outcomes.